(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article aims to briefly rethink the impact of the principle of motivation of judicial decisions on the Brazilian civil procedural system, highlighting the importance of the reasoning of judicial decisions, in order to avoid discretionary and subjective acts, as well as to enforce the principle of due process of law and protect the fundamental rights established in the Magna Carta.